Hi,
Please could you help me with this ztransform question? (See the attachment).
How about this approach?
Z[ y(k+2) ] = z^2*Y(z)  z^2*y(0)  z*y(1)
and
Z[ u(k1) ] = z^1 * U(z)  0 = z^1 * z/(z1)
Then just multiply Z[y(k+2)]*Z[u(k1)]
Is that correct?
Many thanks
Please could you help me with this ztransform question? (See the attachment).
How about this approach?
Z[ y(k+2) ] = z^2*Y(z)  z^2*y(0)  z*y(1)
and
Z[ u(k1) ] = z^1 * U(z)  0 = z^1 * z/(z1)
Then just multiply Z[y(k+2)]*Z[u(k1)]
Is that correct?
Many thanks
Attachments

76.8 KB Views: 14